2018
DOI: 10.1136/bmj.k2739
|View full text |Cite|
|
Sign up to set email alerts
|

Prenatal biochemical screening and long term risk of maternal cardiovascular disease: population based cohort study

Abstract: ObjectiveTo examine whether abnormal prenatal biochemical screening results are associated with an increased risk of premature cardiovascular disease after pregnancy.DesignPopulation based cohort study.SettingThe entire province of Ontario, Canada, where healthcare is universally available.ParticipantsWomen aged 12-55 years, without pre-existing cardiovascular disease, who underwent prenatal screening between 1993 and 2011. One pregnancy per woman was randomly selected.ExposuresLow (≤5th centile multiple of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(51 reference statements)
0
1
0
1
Order By: Relevance
“…Several studies have demonstrated that pregnant women carrying a female fetus, in the absence of chromosomal abnormalities, have higher levels of free b-hCG and pregnancy-associated plasma protein A (PAPP-A). [21][22][23] It is also known that having low first trimester PAPP-A values is associated with increased risk of obstetric complications, such as preeclampsia and maternal long-term cardiovascular diseases, 36,37 and our own data have shown lower levels of PAPP-A in women with SDB compared to controls. 38…”
Section: Fetal Sex and Risk Of Sdb-associated Pregnancy Complicationsmentioning
confidence: 52%
“…Several studies have demonstrated that pregnant women carrying a female fetus, in the absence of chromosomal abnormalities, have higher levels of free b-hCG and pregnancy-associated plasma protein A (PAPP-A). [21][22][23] It is also known that having low first trimester PAPP-A values is associated with increased risk of obstetric complications, such as preeclampsia and maternal long-term cardiovascular diseases, 36,37 and our own data have shown lower levels of PAPP-A in women with SDB compared to controls. 38…”
Section: Fetal Sex and Risk Of Sdb-associated Pregnancy Complicationsmentioning
confidence: 52%
“…Первоначально пренатальный биохимический скрининг у беременных применяли только для диагностики аномалий развития у плода. Однако впоследствии было установлено, что он обладает высокой специфичностью для ранней диагностики высокого риска преэклампсии, а также для оценки долгосрочного риска возникновения тяжелых сердечно-сосудистых заболеваний у женщин [54][55][56]. Было установлено, что чем выше уровни АФП, ХГЧ и ингибина, тем больше вероятность развития преэклампсии и возникновения в будущем сердечно-сосудистой патологии.…”
Section: ингибин как маркер осложнений течения беременностиunclassified